2021
DOI: 10.1080/14763141.2021.1927162
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical energy flow in torso during baseball toss batting

Abstract: The purpose of this study was to clarify the relationship between the efficiency of mechanical energy flow in the torso and bat head speed at impact. Ninety-eight amateur baseball players batted a light ball tossed from the pitcher direction 3.2 m away. The batting motion and ground reaction forces acting on each foot were recorded using a motion capture system and two force plates, respectively. The mechanical powers of the joint forces and joint torques were calculated to measure the generation, absorption, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…The Fast BSV players have their bats controlled by the radial/ulnar deviation action of the wrist joint on the top-hand side as the ball impacts the bat. Thereby, they can transfer a large amount of mechanical energy from the hand to the bat, creating a fast BSV [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…The Fast BSV players have their bats controlled by the radial/ulnar deviation action of the wrist joint on the top-hand side as the ball impacts the bat. Thereby, they can transfer a large amount of mechanical energy from the hand to the bat, creating a fast BSV [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have examined energy flow through the torso during baseball hitting. These combined study results demonstrated that the torso is primarily utilized as a pathway for energy transfer from the proximal lower extremities to the distal upper extremities [2,6,7]. Although prior studies have provided valuable insight, both studies lacked analysis of the upper extremity segments [6,7].…”
Section: Energy Flow During Baseball Machine Hittingmentioning
confidence: 92%
“…Although prior hitting research has predominantly analyzed individual kinematic and kinetic parameters, energy flow analysis of the swing can provide a more comprehensive understanding of how the kinetic chain functions throughout the phases of the swing [1,3,4,8]. Emerging hitting-energy flow studies have primarily focused on proximal segments such as the pelvis and torso, with a limited number examining the upper and lower extremities [2,[5][6][7]9]. Horiuchi et al (2017) recently investigated energy flow in the lower extremities and torso during baseball hitting.…”
Section: Introductionmentioning
confidence: 99%
“…in front of home plate. Performing three maximal effort swings per condition is similar to methods from prior hitting studies [17,22]. At least one minute of rest was allotted in between each swing trial.…”
Section: Methodsmentioning
confidence: 99%
“…Participants performed three trials of maximal effort swings from a stationary tee followed by three maximal effort swings from a front toss with a pitcher located 9.14 m in front of home plate. Performing three maximal effort swings per condition is similar to methods from prior hitting studies 17 22 . At least one minute of rest was allotted in between each swing trial.…”
Section: Methodsmentioning
confidence: 99%